2021
DOI: 10.1111/brv.12735
|View full text |Cite
|
Sign up to set email alerts
|

Temporal resource partitioning mitigates interspecific competition and promotes coexistence among insect parasites

Abstract: A key to understanding life's great diversity is discerning how competing organisms divide limiting resources to coexist in diverse communities. While temporal resource partitioning has long been hypothesized to reduce the negative effects of interspecific competition, empirical evidence suggests that time may not often be an axis along which animal species routinely subdivide resources. Here, we present evidence to the contrary in the world's most biodiverse group of animals: insect parasites (parasitoids). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 232 publications
2
18
0
Order By: Relevance
“…Combining eclosion data across temperature treatments showed that the three hawthorn wasp species differed in their eclosion phenologies (F = 18.75, p = 7.7 × 10 -8 , Fig. S4), as expected from previous research demonstrating temporal niche partitioning within the community (Hood et al 2015, 2021). The relative order of eclosion of the wasps from earliest to latest was Uc, Dm, and Da.…”
Section: Resultssupporting
confidence: 80%
“…Combining eclosion data across temperature treatments showed that the three hawthorn wasp species differed in their eclosion phenologies (F = 18.75, p = 7.7 × 10 -8 , Fig. S4), as expected from previous research demonstrating temporal niche partitioning within the community (Hood et al 2015, 2021). The relative order of eclosion of the wasps from earliest to latest was Uc, Dm, and Da.…”
Section: Resultssupporting
confidence: 80%
“…S3). Specialist parasitoids tend to vary their use of temporal and spatial resources to facilitate coexistence (Hood et al 2021), so more natural enemies on the mainland do not necessary imply higher levels of butterfly larval mortality. The low niche overlap between the two parasitoids on the mainland can be explained by climate, habitat and/or host preferences, differences that may have originated as a result of a phenomenon of competitive exclusion.…”
Section: Variation In Parasitism Pressure and Apparent Competitionmentioning
confidence: 99%
“…It is essential to mention that despite the increase in C. vestalis competitive strength as the temperature increases, it does not necessarily imply that D. semiclausum will be displaced as environmental heterogeneity will favor coexistence of both species (Bonsall et al, 2002;Gols et al, 2005;Hood et al, 2021;Outreman et al, 2018;Poelman et al, 2014;Price, 1972). The study of the effects of ETEs on parasitoid assembly requires a high level of integration across temporal scales (e.g., seasonal), spatial scale (e.g., landscape and patch connectivity), occurrence and magnitude of extremes, and food web structure (e.g., bottom-up and top-down forces) creating multiple possible scenarios (Han et al, 2019;Rosenblatt & Schmitz, 2016;Thierry et al, 2019;Tougeron et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the principle of mutual exclusion, two species with a perfectly overlapping ecological niche cannot coexist in the same environment, and one superior competitor dominates the interaction (Dajoz, 2006). Thus individuals and species tend to reduce their niche overlap by attacking different stages of the same host or shifting their time of activity or spatial niche (Hood et al, 2021). However, environmental filtering is expected to reduce the range of an organism's phenotype (i.e.…”
Section: Consequences For Non-trophic Interactionsmentioning
confidence: 99%
See 1 more Smart Citation